Cooperative Coupling of H2 O2 Production and Organic Synthesis over a Floatable Polystyrene-Sphere-Supported TiO2 /Bi2 O3 S-Scheme Photocatalyst - He, Bowen (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.